Estudo de propriedades físicas de nanocristais de ZnTe e Zn1-xAxTe (A = Mn; Co) no sistema vítreo P2O5 ZnO Al2O3 BaO PbO - Silva, Alessandra dos Santos (2015)
In this work, Zn1-xAxTe (A = Mn, Co) diluted magnetic semiconductors (DMS) nanocrystal (NCs) were successfully grown in the P2O5 ZnO Al2O3 BaO PbO glass system synthesized by the method of Fusion-Nucleation, after subjecting to appropriate thermal annealing. Various experimental techniques were used in this study in order to get a comprehensive understanding of the optical, morphological, structural and magnetic properties these NCs. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) images revealed the size of both of Zn1-xMnxTe and Zn1-xCoxTe NCs. From the vibrating sample magnetometer (VSM) technique, there was growth behavior of magnetization and magnetic susceptibility as a function of the Mn concentration in the samples containing Zn1-xMnxTe NCs. At lower Mn concentrations, the sp electrons of ZnTe host semiconductor interact with the d electrons of Mn2+ ions, resulting in the sp-d exchange interaction, which causes a small increase in susceptibility. At higher Mn concentrations, the d-d exchange interaction between Mn atoms dominates over the sp-d exchange interaction, resulting in an abrupt increase in susceptibility. The EPR spectra, in addition to prove the results exhibited the well-known sextet hyperfine lines of Mn2+ ions, since samples with low Mn concentrations revealed the presence of Mn2+ ions within and near the surface of the ZnTe NCs. From the optical absorption spectra (OA) and photoluminescence (PL), analyzed on the basis of crystal field theory (CFT) as well as of the diffraction X-ray (XRD), Raman scattering (RS) and electron microscopy transmission (TEM) techniques, the substitutional incorporation of Mn2+ ions was confirmed up to its solubility limit (x = 0.100) ZnTe NCs. Above this concentration, can observe the formation of manganese oxide NCs such as MnO and MnO2, since the nucleation rate for the formation of these NCs is greater than that of Zn1-xMnxTe NCs, at high concentrations. Furthermore, from the PL spectra, it was found that it is possible to tune the emission of energy related to transition 4T1(4G) → 6A1(6S) of Mn2+ ions, of the spectral orange region to the near infrared, depending on Mn concentration. This is possible due to the variation of the local crystal field, where these ions are inserted. From the OA spectra, analyzed on the basis of CFT, it showed that Co2+ ions are substitutionally incorporated in tetrahedral sites of ZnTe NCs, due to its characteristics transitions in visible and near infrared spectral region. This evidence has been enhanced from MFM images, since NCs doped with magnetic ions, magnetically respond when induced by the magnetization of the probe.